2020
DOI: 10.3389/fonc.2020.00461
|View full text |Cite
|
Sign up to set email alerts
|

WDHD1 Leads to Cisplatin Resistance by Promoting MAPRE2 Ubiquitination in Lung Adenocarcinoma

Abstract: Ubiquitin ligases have been shown to regulate drug sensitivity. This study aimed to explore the role of the ubiquitin ligase WD repeat and HMG-box DNA binding protein 1 (WDHD1) in regulating cisplatin sensitivity in lung adenocarcinoma (LUAD). A quantitative analysis of the global proteome identified differential protein expression between LUAD A549 cells and the cisplatin-resistant strain A549/DDP. Public databases revealed the relationship between ubiquitin ligase expression and the prognosis of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…The differences in the proteome and potentially miRNA cargoes of these exosomes are most likely the cause for these differences. For example, some proteins with protective effect such as the ribose-phosphate pyrophosphokinase 1 (PRPS1) which is responsible for nucleotide synthesis, and the ubiquitin ligase WD repeat and HMG-box DNA binding protein 1 (WDHD1) were expressed exclusively in the exosomal proteomic cargo of HMPOS-2.5R and may explain their distinct effect on HMPOS-S [ 38 , 39 ]. While it is possible that the delivery and uptake of these proteins were key in promoting drug resistance, it is remained to be determined how other factors contained in the exosomal unit such miRNA might also support this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the proteome and potentially miRNA cargoes of these exosomes are most likely the cause for these differences. For example, some proteins with protective effect such as the ribose-phosphate pyrophosphokinase 1 (PRPS1) which is responsible for nucleotide synthesis, and the ubiquitin ligase WD repeat and HMG-box DNA binding protein 1 (WDHD1) were expressed exclusively in the exosomal proteomic cargo of HMPOS-2.5R and may explain their distinct effect on HMPOS-S [ 38 , 39 ]. While it is possible that the delivery and uptake of these proteins were key in promoting drug resistance, it is remained to be determined how other factors contained in the exosomal unit such miRNA might also support this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…It is a kind of DNA binding protein in the nucleus and cytoplasm, which controls mitosis, DNA damage, and repair. Meanwhile, WDHD1 is also a ubiquitin ligase, which is related to tumor development and malignant phenotype [ 17 , 19 , 30 ].WDHD1 is a human homologue of CTF4 (chromosome transmission fidelity factor 4) in Saccharomyces cerevisiae [ 31 ]. WDHD1 is similar to the sequence of CTF4 (722 of 1129 aligned residues have 21% homology and 36% similarity).…”
Section: Wdhd1mentioning
confidence: 99%
“…The clinical importance of WDHD1 in TNBC was evaluated in samples obtained from TNBC patients, showing that its levels are increased in TNBC compared to normal breast tissues, and associates with tumour size, stage and proliferation, using Ki67 as a proliferation marker 52 . Moreover, recent reports demonstrated that overexpression of WDHD1 leads to cisplatin resistance in lung adenocarcinoma 53 and metastasis in cholangiocarcinoma 54 . Further studies are required to confirm these findings in TNBC.…”
Section: Discussionmentioning
confidence: 99%